Nrf2 activation does not affect adenoma development in a mouse model of colorectal cancer - Elena V. Knatko (Nature Portfolio, 2021)
Knatko et al. examined the importance of Nrf2 activity in the development of colorectal adenomas by performing genetic and pharmacological analyses. The authors found that Keap1 knockdown and Nrf2 activation impacted the metabolism of the non-tumoral colon, but did not affect colorectal adenoma formation in this model.